2014
DOI: 10.1523/jneurosci.5082-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Value Signals in the Prefrontal Cortex Predict Individual Preferences across Reward Categories

Abstract: Humans can choose between fundamentally different options, such as watching a movie or going out for dinner. According to the utility concept, put forward by utilitarian philosophers and widely used in economics, this may be accomplished by mapping the value of different options onto a common scale, independent of specific option characteristics (Fehr and Rangel, 2011; Levy and Glimcher, 2012). If this is the case, value-related activity patterns in the brain should allow predictions of individual preferences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
43
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 24 publications
9
43
1
Order By: Relevance
“…Here, patterns of fMRI activity coding for the predicted value of a sweet odor could be used to reliably classify the predicted value of a savory odor, and vice versa. This finding echoes and extends recent evidence showing that vmPFC activity patterns generalize across different reward categories (4,5,7), such as food items, merchandizing gimmicks, and leisure activities. In these studies, classifiers were trained on exemplars (i.e., different items) associated with different values in one category and could be used to predict the value of exemplars in another category.…”
Section: Discussionsupporting
confidence: 87%
“…Here, patterns of fMRI activity coding for the predicted value of a sweet odor could be used to reliably classify the predicted value of a savory odor, and vice versa. This finding echoes and extends recent evidence showing that vmPFC activity patterns generalize across different reward categories (4,5,7), such as food items, merchandizing gimmicks, and leisure activities. In these studies, classifiers were trained on exemplars (i.e., different items) associated with different values in one category and could be used to predict the value of exemplars in another category.…”
Section: Discussionsupporting
confidence: 87%
“…The lack of cross-task classification in this study stands in contrast to other studies that have demonstrated strong cross-task classification (Eger et al, 2009; Etzel et al, 2008; Lewis-Peacock and Postle, 2008; Meyer et al, 2010; Shinkareva et al, 2011). The lack of cross-task value-level classification success was surprising given previous work demonstrating cross-domain value-level classification (Gross et al, 2014). The lack of cross-task classification in the current study calls for future studies aimed at better defining the conditions under which cross-task classification is possible.…”
Section: Discussionmentioning
confidence: 91%
“…Previous research supported this design. Indeed, several studies have demonstrated robust classification of abstract cognitive processes such as intentions (Haynes et al, 2007; Soon et al, 2008), attention (Rosenberg et al, 2015) and valuation (Gross et al, 2014) to name only a few. Further demonstrating the power of MVPA classifiers, the three-class classification discriminating the cognitive processes of memory retrieval, valuation and perceptual processing performed well above chance in a standard two-way cross-validation applied to the localizer task fMRI data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 However, sensory inputs from the visual, auditory, gustatory, olfactory and somatosensory systems arrive into the OFC primarily in the lateral portions of the orbital surface 22 . Thus, we hypothesized that more lateral parts of the OFC would be especially involved in encoding elemental attributes about a food outcome, in contrast to the medial OFC which we hypothesized would be especially involved in encoding an overall subjective goal-value signal for the foods, as found in many previous reports 1,6,13 .…”
mentioning
confidence: 79%